Influence of adverse factors of low intensity on the frequency of malformations in fetuses and newborns - Olena Vasylivna Vlasova; Mariana Ivanivna Hrytsiuk; Uliana Ivanivna Marusyk (Kazimierz Wielki University, 2020)
Extreme anthropogenic and technology-related environmental factors are known to have an adverse influence on the development of fetal and newborn malformations. The subject has been studied fully enough and is also practically assured. At the same time, the long-term impact of low-intensity factors (each of which does not exceed the maximum permissible concentration) both on the body of parents and the frequency of development (sentinel) structural changes in children has not been discussed in sufficient detail. Based on this, the analysis of the malformations frequency in fetuses and newborns was conducted from 2004 to 2014 if their parents lived in 5 districts of Chernivtsi region and the districts were known as technogenic polluted (ERF 2,0 or more). The obtained data has been compared to the malformations frequency in fetuses and newborns whose parents constantly lived in more favorable environmental conditions (ERF less than 2,0). Accordingly, the data provided make us consider that if parents lived where there was an increased risk of environmental factors influence their body, their children had major (sentinel) malformations more often than the comparison group. These malformations are recommended for mandatory registration in the EUROCAT register. Since these malformations with a fixed phenotype reflect the interaction of genetic and environmental factors, the data obtained, in particular, indicates the correctness of the selected group forming criteria.